Feeding the pyramid builders: Early agriculture at Giza in Egypt - Sheisha, Hader; Kaniewski, David; Marriner, Nick; Djamali, Morteza; Younes, Gamal; Chen, Zhongyuan; El-Qady, Gad; Saleem, Amr; Khater, Carla; Véron, Alain; Anthony, Edward; Abdelmaguid, Mohamed Mustapha; et al. (Quaternary science reviews, 2023)
While the exact technical processes employed in the construction of the pyramids are still a subject of ongoing debate, it is widely recognized that the Giza Plateau served as a hub where various trades converged with the common objective of building the necropolis. Of particular importance was the development of a local and sustainable food supply for the thousands of laborers involved in this monumental undertaking. Here, we explore the long-term behavioural mechanisms that led human societies to gradually colonize the Nile swamps at Giza. They developed herding and farming, paving the way for greater human exploitation of the area during the Dynastic Egypt. We show that transhumance tribes, originally from the Eastern Sahara, settled along the Giza Plateau 5200 years ago, primarily engaging in herding and, more sporadically, agriculture. Giza was transformed into a pastoral landscape, with the development of large swaths of the floodplain, providing societies with permanent access to livestock produce (e.g. proteins, milk, meat and wool). Our palaeoecological data reveal that the initial complex societies at Giza were deeply rooted in transhumance, pastoralism and animal husbandry. These activities played a fundamental role in establishing the foundations of a robust and sustainable food system, while also serving as a crucial logistical support for the subsequent construction of the monumental structures that celebrated the grandeur of pharaonic Egypt. •Two cores extracted from the Khufu branch of the Nile at Giza.•A 7600-year record of agropastoral activities from the pyramids area.•Insight into the first complex societies at Giza.•The area was mainly a pastoral landscape when the necropolis was built.•The Third Intermediate Period was the worst phase for agropastoral activities.